A study on customer satisfaction on e-payment applications - CHERUKUR, MR.RAM BABU; HARSHITHA P, Ms. SRILAKSHMI (The journal of contemporary issues in business and government, 2020)
The present study focuses on the customer satisfaction towards mobile wallets. This study examines the factors that influence customers satisfaction while using mobile wallets. Nowadays everyone uses their smartphones to make their day today transactions using mobile wallets. Mobile wallets create a huge impact among the people. The present study is carried by a survey conducted among the mobile wallet users to identify the satisfactory levels of them. The study focuses on the level of satisfaction and factors that satisfy the customers in using mobile wallets.